Politics and Pragmatism in Early North American Folklore Scholarship - H. Carpenter, Carole (Ethnologies, 1991)
This paper relates differences between the development of Folklore Studies, especially in national institutions, in Canada and the U.S. A. to disparate sociopolitical and pragmatic concerns in either nation. The different approaches and activities of Franz Boas and Marius Barbeau are used as examples, with specific reference made to their involvement with the Northwest Coast native people and their potlatch tradition.